Counseling About Disinfection During Repair of Acrylic Resin Dentures at Dental Laboratories in Malang and Kediri - Dwiyanti Feriana Ratwita (Darmabakti Cendekia: Journal of Community Service and Engagements, 2021)
Background: Sometimes the artificial teeth break or fracture, so then the patient asks the dentist to repair  it. The dentist will then send the denture to be repaired by a dental technician in the dental laboratory. The transfer of work is likely to pose a risk of cross infection (for example: AIDS, hepatitis, tuberculosis, pneumonia and herpes. Objective: To transfer knowledge and technology of dentistry based on community needs objectively to obtain a strong foundation in carrying out health management of dental technicians . Implementation Method: Providing counseling to dental technicians on how to use disinfection materials and using props accompanied by interactive discussion Results: Implementation this programs  is conducted at 2 locations in the city of  Malang and Kediri Counseling is done by providing knowledge about how to disinfect dentures using chlorhexidine material by spraying it on the entire surface of the denture. Conclusion: The counseling activity which was held for a day received good reception from the participants.The dedication report was prepared to be a reference material in raising awareness of t dental technicians who work in dental laboratories to avoid cross-infection when doing denture repair